2012
DOI: 10.1073/pnas.1201370109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mass transfer on the oxygen reduction reaction catalyzed by platinum dendrimer encapsulated nanoparticles

Abstract: Here we report on the effect of the mass transfer rate (k t ) on the oxygen reduction reaction (ORR) catalyzed by Pt dendrimer-encapsulated nanoparticles (DENs) comprised of 147 and 55 atoms (Pt 147 and Pt 55 ). The experiments were carried out using a dual-electrode microelectrochemical device, which enables the study of the ORR under high k t conditions with simultaneous detection of H 2 O 2 . At low k t (0.02 to 0.12 cm s −1 ) the effective number of electrons involved in ORR, n eff , is 3.7 for Pt 147 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 42 publications
7
48
0
6
Order By: Relevance
“…The same effect was also demonstrated for other reactions that feature Figure 6. [217] A constant H 2 O 2 yield with flow rate was also observed by Behm and co-workers for extended polycrystalline Pt surfaces (see Figure 5 c in reference [48]), consistent with the results of Dumitrescu and Crooks. As the inter-NP distance is decreased, the diffusion spheres start to overlap.…”
Section: Influence Of Mass Transportsupporting
confidence: 88%
See 1 more Smart Citation
“…The same effect was also demonstrated for other reactions that feature Figure 6. [217] A constant H 2 O 2 yield with flow rate was also observed by Behm and co-workers for extended polycrystalline Pt surfaces (see Figure 5 c in reference [48]), consistent with the results of Dumitrescu and Crooks. As the inter-NP distance is decreased, the diffusion spheres start to overlap.…”
Section: Influence Of Mass Transportsupporting
confidence: 88%
“…[48] The amount of hydrogen peroxide detected downstream diminished as the NP density was increased and/or the flow rate was reduced (i.e. [216,217] A key attribute to this type of cell is that the hydrodynamics are very well defined and transport can be varied and controlled over a wide range. The same effect was also demonstrated for other reactions that feature Figure 6.…”
Section: Influence Of Mass Transportmentioning
confidence: 99%
“…Interestingly, with a series of Pt nanoparticles containing an average of 55, 100, 147, 200 and 240 Pt atoms, they found that the largest particles exhibited the highest specific activities [47]. In a following research effort, the effect of mass transfer on ORR catalyzed by Pt 55 and Pt 147 dendrimer encapsulated particles was also investigated by them [48].…”
Section: Pt Clusters For Orrmentioning
confidence: 99%
“…If n = 4, which is reasonable with mass transport of this magnitude [39], we obtain k t = 0.06 cm s −1 , although it should be noted that the effective n may be lower. This is a relatively high mass transport rate and provides a means of determining ORR kinetics [39][40][41]. Fig.…”
Section: Orr On Low Density Swnt/pt Compositesmentioning
confidence: 99%